Increasing Student Understanding and Concentration Through Virtual Reality Learning Media in Electronic Records Management Courses - Andi Basuki; Novel Pradewa Christanto (CV. AFDIFAL MAJU BERKAH, 2023)
Technology development today gives students many references to learn new things. The development of technology-based learning media is an alternative for teaching staff to make a breakthrough in the world of education. Virtual Reality is a technology that can make its users feel like they are in another room without having to move. This technology is supported with audiovisual features, which can make users feel isolated and focus on VR media. The purpose of developing this VR learning media is to measure students' understanding of the material presented in VR learning media and to measure student concentration when using VR learning media. This research was conducted on students from the State University of Malang who taught the Electronic Records Management course. Learning media adapts from sub-CPMK to 1.1. The development of this VR learning media uses the multimedia development method from Luther. The results of the material expert validator and media expert show that learning media is very suitable for learning media by getting a score of 94%. The results obtained from this study show that learning media influences students' understanding of the material, which is indicated by an increase in the class average at the learning stage. Post-test by 11%. This study also found that this learning media made students concentrate more because they felt more focused when using Virtual Reality.